Fabrication of Mambong pottery by using slip casting method - A.I.A. Termizi; J.J. Mohamed (Universiti Malaysia Kelantan, 2016)
Mambong pottery in Kuala Krai, Kelantan is one of the types of potteries in Malaysia other than Sayong, Terenang and Sarawak pottery. Mambong pottery was being made by traditional technique like pinching and throwing. In this research, Mambong pottery was made by using slip casting method. This method used porous mould which can absorb the water content from the clay slip. Different composition of water and clay was used and its effect on product properties was investigated. Samples with different composition of water and clay were labelled as 50C50W, 60C40W, 70C30W and 80C20W samples with addition of 0.7% of sodium silicate, Na2SiO3. The samples were characterized by its specific gravity (S.G.) of clay slip, drying and firing linear shrinkage, density and porosity and strength of the clay samples. Finding from this research showed that 70C30W sample is the optimum composition in fabricating pottery by using slip casting among other samples.